Reliability of static and dynamic balance assessments using the FootWork Pro pressure® platform in a clinical setting - van Gulick, D.; van der Leeden, M.; Lucas, C.; Stuiver, M. (Journal of Science and Medicine in Sport, 2025)
Objectives The objective of this study was to evaluate the reliability and feasibility of static and dynamic balance assessments using the FootWork Pro® pressure platform in healthy adults, along with the impact of protocol variations on reliability.